Association of chronic diseases and lifestyle factors with suicidal ideation among adults aged 18-69 years in Eswatini: evidence from a population-based survey - Mfundi President Sebenele Motsa; Hung-Yi Chiou; Yi-Hua Chen (BMC, 2021)
Abstract Background How chronic diseases and lifestyle affect suicidal ideation in the sub-Saharan region remains unclear. We investigated the association of chronic diseases and lifestyle with suicidal ideation in the past year and the potential modifying role of sociodemographic status on this association. The findings can guide suicide prevention interventions. Methods We analyzed 3026 respondents from the World Health Organization STEPwise approach to noncommunicable disease risk factor surveillance conducted in Eswatini in 2014. The outcome was past-year suicidal ideation, and the main predictors were chronic diseases and lifestyle. Multiple logistic regression was used to estimate predictors, and subgroup analysis was performed to assess effect modification. Results The prevalence of past-year suicidal ideation was 9.9%. After adjustment for covariates, including sex, marital status, employment status, and education level, individuals aged 18-30 years (adjusted odds ratio [aOR]: 2.27, 95% confidence interval [CI]: 1.22-4.22) were more likely to have had past-year suicidal ideation than those aged 45-69 years. After adjustment for covariates among employed individuals, having high blood pressure (aOR: 3.38, 95% CI: 1.54-7.40), not exercising (aOR: 2.65, 95% CI: 1.09-6.39), drinking alcohol (aOR: 2.40, 95% CI: 1.14-5.05), being aged 18-30 years (aOR: 3.50, 95% CI: 1.01-12.1), and being exposed to threats (aOR: 2.37, 95% CI: 1.01-5.53) were significantly associated with past-year suicidal ideation. Conclusions Among currently employed individuals, having high blood pressure, not exercising, and drinking alcohol were associated with past-year suicidal ideation. The findings highlight the importance of developing and strengthening systems for early identification of suicidal ideation risk.